A qualitative study on language acquisition of female learners / Parilah M. Shah - M. Shah, Parilah (2002)
This qualitative study investigated the underachieving female learners' perceptions regarding their English as a Second Language (ESL) learning at University Kebangsaan Malaysia. It examined the views that these language learners held of their language acquisition and learning experiences as related to sociocultural influences, formal instruction and language education policy. A naturalistic approach was utilized during the investigation. The data were gathered through conducting in-depth interviews, making observations, reviewing relevant documents, and utilizing other supplementary techniques. The researcher used Strauss and Corbin's (1990) coding paradigm (i.e. open coding and axial coding) to analyze the data. The results of this investigation revealed that several variables impacted the female students' underachievement. Among the findings were negative peers' reaction and behaviour, community's influence, unsuitable lesson time, large class size, and unclear as well as unjustifiable policy.